1988
DOI: 10.1111/j.1469-7610.1988.tb01886.x
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Adversity and Recent Stressful Life Events in Anxious and Depressed Children

Abstract: Poor confiding relations in mothers' own lives, the presence of maternal distress and recent stressful life events focussed on children are all significantly and independently associated with emotional disorder in the school-age child. The probability of being a case is best predicted by considering the contribution of all three factors. When this is done, an additive rather than multiplicative interaction for the three variables is found. The association between these maternal factors and events focussed on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
34
0
1

Year Published

1993
1993
2011
2011

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(38 citation statements)
references
References 12 publications
3
34
0
1
Order By: Relevance
“…This is surprising given that as most anxiety disorders take a chronic course, environmental factors important to onset are likely to be those present in childhood (Rapee and Bryant 2008). The limited evidence available indicates that anxious children experience a greater number of life events and some specific chronic adversities in the 12-month period preceding the onset of anxiety in comparison to healthy controls (e.g., Goodyer et al 1988Goodyer et al , 1990.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…This is surprising given that as most anxiety disorders take a chronic course, environmental factors important to onset are likely to be those present in childhood (Rapee and Bryant 2008). The limited evidence available indicates that anxious children experience a greater number of life events and some specific chronic adversities in the 12-month period preceding the onset of anxiety in comparison to healthy controls (e.g., Goodyer et al 1988Goodyer et al , 1990.…”
mentioning
confidence: 99%
“…First, in two of the studies anxious children were identified by an unstructured psychiatric interview and were obtained from severely disturbed populations attending in-patient and outpatient hospital-based psychiatric clinics (Goodyer et al 1988(Goodyer et al , 1990, which is not characteristic of most anxious children. The only study to identify children using a structured psychiatric interview (Gothelf et al 2004) relied on a child self-report checklist to assess life events and thus failed to provide a more independent determination of the "severity" or impact of stressors.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Stress is another aspect of the family context that is likely to be heightened among children of mothers with depressive symptoms. Prior to the development of depression or conduct disorder, youth have been found to report the presence of more stressful life events (Goodyer, Wright, & Altham, 1988;Hastings, Anderson, & Kelley, 1996).We chose to study mediation as youth transition into early adolescence (Grades 5-6, as defined by Forehand, Neighbors, & Wierson, 1991), This age period was chosen in part because it marks a time of change and transition that can negatively influence individuals (Simmons, Burgeson, Carlton-Ford, & Blyth, 1987) and is associated with an increase in problems (Petersen & Hamburg, 1986 (Montemayor, 1986).The first proposed mediator in this study is mother-child communication. Parents play a pivotal role in their children's social and emotional competence by coaching, teaching, and nurturing developing skills (e.g., Parke, MacDonald, Beitel, & Bhavnagri, 1988).…”
mentioning
confidence: 99%
“…Surprisingly, and despite the ongoing interest in the role of stressful events in depression, there is a scarcity of research with clinical samples of diagnosed depressed youth. We identified only four studies of depressed pediatric samples that compared clinical cases with normal controls (Goodyer et al, 1988;Horesh et al, 2003;, and two studies that compared depressed youths and youths with other psychiatric diagnoses (Benfield et al, 1988;Berney et al, 1991). However, these studies have included small samples, which constrain both the interpretation and generalizability of the findings.…”
Section: Introductionmentioning
confidence: 99%